Evaluation the correlation between Inulin and Cystatin C with kidney function tests and GFR in patients with renal disorders - Nawar Mohsin Abd-alaziz; Wasan Nazhan Hussein (Tikrit Journal of Pure Science)
Background: Kidneys are important organs in the human body because of their great importance in assisting the body to remove waste products that resulting from food metabolism through renal filtration of blood plasma from unwanted substances and excreted through diuresis and recover substances that body needs to the blood, relative effectiveness of the kidney can be estimated by measuring the efficiency of glomerular filteration rate (GRF), represented by amount of inulin filtrate into renal tubules for a specified period of time, any difference in normal value indicates the presence of a disorder in the kidney, which affects on performance of its functions and occurrence of imbalance in internal environment of the body, and leads to disrupting functions of other parts of the body, measuring rate of renal filtration is one of the best ways to know function of the kidneys and diagnose various kidney diseases and prevent their development.